Implementasi Terapi Dzikir Dalam Asuhan Keperawatan Pada Pasien Dengan Halusinasi Pendengaran Di Rumah Sakit Jiwa Prof. Dr. M. Ildrem Sumatera Utara - Irma Widya Putri; Rafika Nur Siregar (STIKES Columbia Asia Medan, 2025)
Auditory hallucinations are a common sensory perception disorder in patients with mental disorders. Dhikr therapy as a non-pharmacological intervention is proven to have a calming effect and help patients focus more on reality. A case study was conducted on one patient at Prof. Dr. M. Ildrem Mental Hospital in North Sumatra for seven days using the nursing process approach. Evaluation results with the AHRS scale showed a decrease in scores from 25 to 13. Patients experienced a decrease in the intensity of hallucinations and increased self-control. The conclusion of this case study is that dhikr therapy is effectively applied in mental nursing care as a nonpharmacological intervention to help patients control auditory hallucinations.